Atención al usuario en el Hospital Martín Icaza de Babahoyo - Placencio Faria, Keila Mireya (2020)
The research was carried out at the Martin Icaza Hospital, an institution in charge of offering medical services that improve the state of health and quality of life of the inhabitants of the Babahoyo canton through the development of competencies of their human talent in terms of service vocation. , teamwork and commitment to users; The objective of the work is to analyze how the sufficiency of the personnel, labor competencies, asset management and the empathy of the institution's personnel, cause that the attention to the users deteriorates and makes it impossible to access the health care services offered by the hospital. The methodology used in the case study is conformed by the type of descriptive and exploratory research, the inductive method was also applied because it helped the analysis of the main findings obtained, together with the survey technique aimed at administration personnel and patients who continuously attend the organization and, as an instrument, a questionnaire for data collection. The results showed that the institution does not have sufficient personnel in the Emergency Area to attend in a timely manner to the demand of patients, the scheduling of appointments is inadequate, where the person who attends the medical review is not attended due to absence of the health professional, in addition the administration of the fixed assets and other materials presents problems, because there is not an opportune number of beds to attend to all the patients.